"The Local Consultant Will Not Be Credible": How Epistemic Injustice Is Experienced and Practised in Development Aid. (2nd September 2020) - Koch, Susanne
ABSTRACT: This paper uses the concept of epistemic injustice to shed light on the discriminatory treatment of experts in and by development aid. While the literature on epistemic justice is largely based on philosophical reasoning, I provide an empirical case study which substantiates theoretical claims with findings from social science research. Drawing on expert interviews conducted in South Africa and Tanzania, I reveal how epistemic injustice is experienced, practiced and institutionalised in a field which claims to work towards global justice. Focusing on aid-related advisory processes, the paper highlights how epistemic authority therein is tied to identity-based prejudice. The systematic credibility deficit policy experts from aid-receiving countries suffer is closely interrelated with the credibility excess so-called 'international' experts profit from. Their privilege is backed by an imaginary that maintains the idea of Northern epistemic superiority and sustained by prevailing employment and procurement practices of donor organisations. The paper suggests that the concurrence of testimonial and hermeneutical injustice prevents experts from the Global South from taking the lead in interpreting their own societies' realities. This, I argue, is not only detrimental to the countries whose knowers are marginalised but also a root cause of persisting global inequality.